2021
DOI: 10.21203/rs.3.rs-243773/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mobile technology as a health literacy enabler in African rural areas: a literature review

Abstract: Background: Since the launch of mobile phones three decade ago, the latter have been used to support healthcare systems through various mobile health (m-health) applications. In recent years, multiple mobile phone-based health projects and applications have emerged. Despite the great enthusiasm around m-health, few studies have examined the use of cell phones to improve health literacy in Africa. This paper aims to review studies related to the contribution of mobile technologies in improving health literacy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…However, in implementing mobile-based health interventions in low-and medium-income countries (LMIC), the social, economic, and cultural factors must be considered to make them more effective. Particularly, much attention has to be paid to rural areas where the majority of people are poor and lack formal education (6).…”
Section: Introductionmentioning
confidence: 99%
“…However, in implementing mobile-based health interventions in low-and medium-income countries (LMIC), the social, economic, and cultural factors must be considered to make them more effective. Particularly, much attention has to be paid to rural areas where the majority of people are poor and lack formal education (6).…”
Section: Introductionmentioning
confidence: 99%
“…Data from 43 countries in SSA have shown that improving the quality of governance improves health outcomes in terms of reducing under five mortality rates, for example [13]. In SSA, mobile phone technology has been used as an intervention to improve health literacy for sexual reproductive health, maternal and child health, Ebola, tuberculosis and malaria [14]. In terms of healthy cities, health faciities located close to communities have shown higher odds of facility delivery for pregnant women and lower odds of neonatal mortality [15].…”
Section: Introductionmentioning
confidence: 99%